Impact of dynamic changes in MELD score on survival after liver transplantation – a Eurotransplant registry analysis. (14th March 2016) - Györi, Georg P.; Silberhumer, Gerd R.; Rahmel, Axel; de Vries, Erwin; Soliman, Thomas; Zehetmayer, Sonja; Rogiers, Xavier; Berlakovich, Gabriela A.; ,
Abstract: Background & Aims: With restricted numbers of available organs, futility in liver transplantation has to be avoided. The concept of dynamic changes in MELD score (DeltaMELD) has previously been shown to be a simple tool to identify patients with the greatest risk of death after transplantation. Aim was to validate this concept with the Eurotransplant (ET) database. Methods: A retrospective registry analysis was performed on all patients listed for liver transplantation within ET between 2006 and 2011. Patients <18 years of age, acute liver failure, malignancy and patients listed for retransplantation were excluded. Influence of MELD at listing (MELDon), MELD at transplantation (MELDoff), DeltaMELD, age, sex, underlying disease and time on the waiting list on overall survival after liver transplantation were evaluated. Results: A total of 16 821 patients were listed for liver transplantation, 8096 met the inclusion criteria. Age, MELD on and DeltaMELD showed significant influence on survival on the waiting list. Age and DeltaMELD showed influence on survival after liver transplantation, with DeltaMELD>10 showing a 1.6‐fold increased risk of death. Conclusion: The concept of DeltaMELD was validated in a large, prospective data set. It provides a simple tool to identify patients with increased risk of death after liver transplantation and might help improve long‐term results. Abstract : See Editorial on Page949